Anion‐Exchange Membranes for Alkaline Fuel‐Cell Applications: The Effects of Cations. Issue 1 (5th December 2017) - Sun, Zhe; Lin, Bencai; Yan, Feng
Abstract: Alkaline anion‐exchange membrane fuel cells (AEMFCs) are attracting much attention because of their potential use of nonprecious electrocatalysts. The anion‐exchange membrane (AEM) is one of the key components of AEMFCs. An ideal AEM should possess high hydroxide conductivity and sufficient long‐term durability at elevated temperatures in high‐pH solutions. Herein, recent progress in research into the alkaline stability behavior of cations (including quaternary ammonium, imidazolium, guanidinium, pyridinium, tertiary sulfonium, phosphonium, benzimidazolium, and pyrrolidinium) and their analogous AEMs, which have been investigated by both experimental studies and theoretical calculations, is reviewed. Effects, including conjugation, steric hindrance e, σ–π hyperconjugation, and electrons, on the alkaline stability of cations and their analogous AEMs have been discussed. The aim of this article is to provide an overview of some key factors for the future design of novel cations and their analogous AEMs with high alkaline stability. Abstract : Long‐lasting separation : The alkaline stability of an anion‐exchange membrane (AEM) is fundamentally affected by the chemical structure of the cationic groups. The alkaline stability behavior of organic cations has been recently investigated by both experimental studies and theoretical calculations. This Minireview provides an up‐to‐date summary and comparison among various organic cations in terms of the alkaline stability and analogous cation‐based AEMs